Development aid to water management in Mali: the actors, ‘global’ paradigms, and ‘local’ translations - Cherlet, Jan (Afrika Focus, 2012)
The four empirical articles experiment with different theoretical concepts to present the data. Starting with a genealogical description of the Capacity Building paradigm in the first empirical article, the theorizing subsequently demonstrates that this paradigm gets translated in numerous ways. The third empirical article shows the importance of individual agency in the implementation of the IWRM paradigm, and the last relies on full-blown Actor-Network Theory to describe the network – widespread in time and space – that supports the IWRM paradigm. Although each theoretical perspective emphasizes different aspects of the data, Actor-Network Theory turns out to be the most apt tool to describe the eclectic set of data that was obtained from multi-sited ethnography, interviews, focus group discussions and documents.